Storm surge changes around the UK under a weakened Atlantic meridional overturning circulation - Tom Howard; Matthew D Palmer; Laura C Jackson; Kuniko Yamazaki (Environmental Research Communications, 2024)
Climate model projections of future North Atlantic storm track changes under global warming are very uncertain, with models showing a variety of responses. Atmospheric storms force storm surges which are a major contributor to coastal flooding hazard in the UK, and so it is important to know how this process might be influenced by climate change—not only what future is probable, but what is possible? As a contribution to answering that question, we drive a simplified model of the north-west European coastal shelf waters with atmospheric forcing taken from climate simulations with HadGEM3-GC3-MM (1/4 degree ocean, approx. 60 km atmosphere in mid-latitudes) which exhibit a substantial weakening of the Atlantic Meridional Overturning Circulation (AMOC). The first is a ‘hosing’ simulation in which a rapid shut-down of the AMOC is induced by modelling the addition of freshwater to the North Atlantic. The second is the HadGEM3 GC3.05 perturbed parameter ensemble simulation under Representative Concentration Pathway 8.5 (RCP 8.5) which was used to inform the UK Climate Projections 2018 (UKCP18). This model has a high climate sensitivity and exhibits substantial weakening of the AMOC. We find substantial simulated increases at some sites: up to about 25% increase in the expected annual maximum meteorological component of the storm surge. In both the hosing simulation and the ensemble simulation, the greatest projected increases are seen at some west coast sites, consistent with strengthening of the strongest westerly winds. On the south-east coast, projected changes are smaller in the hosing simulation and generally negative in the ensemble simulation. The ensemble simulation shows a decrease in the strongest northerly winds as well as the growth in the westerlies. Overall, these low-likelihood increases over the 21st century associated with storminess are smaller than the likely contribution from mean sea-level rise over the same period, but, importantly, larger than the so-called “high-end” changes associated with storminess that were reported in UKCP18.